"Take It Outside, People!": Bridging Ecoacoustics and Improvised Music - Whitehead, Glen C. (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
The era of COVID-19 has profoundly shaken the foundations of our lives. Our event venues have closed; the support systems that we depend on for delivering works of art have all been shuttered. In response, musicians have turned to the digital world. While the digital world has become an important collaborative interface, I believe it is imperative to also explore the opposite direction—and take it outside! Even pre-COVID-19, it has been important to expand musical methodologies by connecting music creation systems with environmental sound practices in new ways. As recent developments in technology have opened up the possibilities of new types of environmentally based artistic engagement, artists of all kinds increasingly feel a profound need to participate in climate crisis activism through creative work.Immersive participation is at the center of the fields of ecoacoustics, soundscape ecology, and related fields. These practices involve acts of listening and responding in participatory environmental engagement. Meanwhile, the field of critical improvisation has expanded from methodologies rooted in music and other arts to connect to a tapestry of multidisciplinary enquiries. I postulate that a shared fundamental human musical “task-scape” lies deep within the behavior systems of both improvised music and environmentally based sound practices. Both areas are constructed with methodologies for engaging with interactive dynamics of the unexpected, and both explore the profound phenomena between the observer and sound.  In this article, I will illuminate how to bring these fields together in new ways by connecting pedagogies and practices within these arenas. Moreover, I will connect these to some of the more profound issues of our time through methodologies of improvised music and ecoacoustics to create new opportunities for performance and practice during and after COVID-19 as well as offer new types of research and artistic expression in regard to climate crisis.